Polarization Criterion in Targeted SETI Observation - Jian-Kang Li; Yu Chen; Bo-Lun Huang; Zhen-Zhao Tao; Xiao-Hang Luan; Xiao-Hui Sun; Tong-Jie Zhang; Vishal Gajjar (The Astronomical Journal, 2023)
In this paper, we propose a novel method for distinguishing extraterrestrial intelligence (ETI) signals from radio frequency interference (RFI) by leveraging polarization features. We exploit the sinusoidal variation of the linearly polarized components of Stokes parameters with the parallactic angle as a characteristic signature of ETI signals, while such linearly polarized components remain relatively stable for terrestrial RFI. Typically, a minimum of 4–8 hr of observation time is required to detect these sinusoidal variations. The polarization approach in the search for extraterrestrial intelligence also enables us to study the radio stellar bursts emitted by M-type stars as ancillary science, which is relevant to assessing the habitability of exoplanets. Compared to the frequency drift method, the polarization method effectively reduces the required observation time for signal identification while improving the signal identification process.